Comparative Analysis of English and Uzbek Terminological Lexicography: Theory, Practice, and Future Directions (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article examines the structure, development, and challenges of terminological lexicography in English and Uzbek. Through comparative analysis, it explores terminographic methodologies, lexical formation, and the integration of terminology into academic and professional discourse. A methodological framework was developed to assess terminological dictionaries, and a corpus-based analysis was conducted to evaluate consistency and standardization. The study highlights linguistic, cultural, and technical barriers in the terminological lexicography of both languages and provides recommendations for harmonization and development.